Letter (copy) : International Solidarity Fund - Tewson, Vincent
032-0023-001 Secretary's. HVT/FC/EK/758. 12th March, 1940., Mr. J. Lewis, Dear Mr. Lewis, INTERNATIONAL SOLIDARITY FUND. Very many thanks for your kind letter in reply to our previous communication. In view of what you say we are retaining your £2, and the very best possible use will be made of your donation to assist the position of refugees who fought for Spain. Yours sincerely, Assistant Secretary. 292/946/32/23